Upper Carboniferous spiriferid brachiopods from Karavanke Mountains, Slovenia - Katarina Pavla Anko (Geologija, 2007)
The paper provides a description of the Upper Carboniferous spiriferid brachiopods from Gornjesavski muzej Jesenice (Permanent paleontological exhibition assembled by Jože Bedič and fossils stored in its depot) and attempts to make a synthesis of earlier and contemporary work in this discipline.